Cross‐sectional and longitudinal epidemiological studies of Internet gaming disorder: A systematic review of the literature - Mihara, Satoko; Higuchi, Susumu (Psychiatry and clinical neurosciences, 2017)
Aim The diagnostic criteria of Internet gaming disorder (IGD) have been included in section III of DSM‐5. This study aims to systematically review both cross‐sectional and longitudinal epidemiological studies of IGD. Methods All publications included in PubMed and PsychINFO up to May 2016 were systematically searched to identify cross‐sectional studies on prevalence and longitudinal studies of IGD. In the process of identification, articles in non‐English languages and studies focusing solely on the use of gaming were excluded, and those meeting the methodological requirements set by this review were included. As a result, 37 cross‐sectional and 13 longitudinal studies were selected for review. Results The prevalence of IGD in the total samples ranged from 0.7% to 27.5%. The prevalence was higher among males than females in the vast majority of studies and tended to be higher among younger rather than older people in some studies. Geographical region made little difference to prevalence. Factors associated with IGD were reported in 28 of 37 cross‐sectional studies. These were diverse and covered gaming, demographic and familial factors, interpersonal relations, social and school functioning, personality, psychiatric comorbidity, and physical health conditions. Longitudinal studies identified risk and protective factors, and health and social consequences of IGD. The natural course of IGD was diverse but tended to be more stable among adolescents compared to adults. Conclusion Although existing epidemiological studies have provided useful data, differences in methodologies make it difficult to compare the findings of these studies when drawing consensus. Future international studies using reliable and uniform methods are warranted.